2007
DOI: 10.1108/02632770710772450
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attributes of hospital multi‐bed wards and preferences for privacy

Abstract: Purpose -The purpose of this article is to explore the relationship between measures of the plan configuration of buildings (in this case multi-bed wards), and subjective judgements on spatial locations for privacy. Design/methodology/approach -Measures of plan configuration from six generic ward designs have been made using space syntax software (visibility graph analysis and depth map). Subjective judgements have been assessed by means of a questionnaire. Findings -Participants' chosen locations for privacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
0
41
1
Order By: Relevance
“…As a result, the findings of these studies in dealing with the relationships between the network of spaces, on the one hand, and psychological responses and behavior, on the other, are less context-dependent and more generalizable [1,2,3,4,5,6,7,8,9,10,11,12]. Several space syntax studies to date, including the ones reported here, show strong relationships between spatial network measures and environmental behavior and psychology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the findings of these studies in dealing with the relationships between the network of spaces, on the one hand, and psychological responses and behavior, on the other, are less context-dependent and more generalizable [1,2,3,4,5,6,7,8,9,10,11,12]. Several space syntax studies to date, including the ones reported here, show strong relationships between spatial network measures and environmental behavior and psychology.…”
Section: Introductionmentioning
confidence: 99%
“…In their earlier study using integration and control, Alalouch and Aspinall [1] investigated locational effects on perceived privacy in six different types of multi-bed units in the UK. A group of 79 subjects were asked to complete a questionnaire on privacy and to select preferred and disliked locations on plans of hospital wards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alalouch & Aspinall (2007) investigated perceived privacy in nursing units in relation to spatial centrality measured using Space Syntax techniques in six different types of multi-bed units in UK.…”
Section: Studies Involving Psychology and Unit Layout Featuresmentioning
confidence: 99%
“…Additionally, patient's preferences for privacy seems to be neglected by the surveyed documents. In a previous study Alalouch et al [33], [34] found that two quantitative measures of the spatial configuration of generic hospital wards -i.e. integration and control-are associated with people preferences for locational privacy.…”
Section: Hierarchy Of Placementioning
confidence: 99%